Evaluation of poly(diaryloxyphosphazene) elastomer for heat shielding insulations and morphology of charred layers. (May 2017) - Zhang, Shuangkun; Wang, Jiqiang; Zhu, Hongchun; Ali, Shafqat; Ma, Hanlin; Zhang, Liqun; Wu, Dezhen; Wu, Zhanpeng
The ablative properties of elastomeric insulations are often inadequate for solid rocket motor (SRM) applications. These materials exhibit relatively high erosion rates during the operation of an SRM unless the charred insulation layers are reinforced with suitable fibre fillers. As alternatives to traditional synthetic rubber materials, flexible semi-inorganic rubbers such as polyphosphazene elastomers are now used as state-of-the-art heat-shielding materials. We have successfully managed to prepare a poly(diaryloxyphosphazene) elastomer (PDPP) as well as some insulation materials that are free of any fibrous fillers (with only the addition of inorganic oxides, such as fumed silica and zinc oxide). These polyphosphazene insulations exhibit excellent linear ablation rates (0.08 mm s −1 after a 20 s ablation test) as compared to synthetic organic rubbers. In addition, integrated and rigid charred layers without noticeable swells are formed on the surfaces of the matrices resulting in 'coral fleece-like' hollow microtubes, which show better ablative resistance performance than do traditional insulations. The pyrolysis products of PDPP have been characterized by pyrolysis gas chromatography mass spectrometry and the mechanism of its decomposition is also discussed.